A study of why Unilever Bangladesh Ltd. is switching from the existing Management Information System (MIS) - matrix to a new MIS- TM1 - Shareef, Tasnim (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.